2022
DOI: 10.1002/hsr2.523
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Clinical Characteristics and Risk Factors Associated with Severe Disease Progression among COVID‐19 Patients In Wad Medani Isolation Centers: A Multicenter Retrospective Cross‐Sectional Study

Abstract: Background Since December 2019, (COVID‐19) has had a significant impact on global health systems. Because little is known about the clinical characteristics and risk factors connected with COVID‐19 severity in Sudanese patients, it is vital to summarize the clinical characteristics of COVID‐19 patients and to investigate the risk factors linked to COVID‐19 severity. Objectives We aimed to assess the clinical characteristics of COVID‐19 patients and look into risk factors associated with COVID‐19 severity. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In comparison with patients with a non-severe form of COVID-19 disease, there was a higher risk in patients with the severe form of COVID-19 with several comorbidities associated. Our results showed that cerebrovascular disease had the highest OR value of 2.76 (95 % CI: 1.65–4.62; I 2 = 44 %; p = 0.06) [ 19 , 21 , 28 , 31 33 , 38 40 , 44 , 45 ] despite the fact that no significant difference between patients with severe and non-severe cerebrovascular disease was reported after analysis. This risk is followed by chronic kidney disease (CKD), with an OR of 2.27 (95 % CI: 1.26–4.06]; I 2 = 96 %; P < 0.001) [ 15 , 18 , 19 , 22 , 24 , 26 35 , 37 , 38 , 42 , 44 , 45 ], hypertension with an OR of 2.22 (95% CI: 1.72–2.87; I 2 = 96 %; p < 0.001) [ 14 40 , 42 46 ] and coronary heart disease with an OR of 2.17 (95 % CI: 1.42–3.31; I 2 = 98 %; p < 0.001) [ 15 , 18 22 , 24 46 ].…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…In comparison with patients with a non-severe form of COVID-19 disease, there was a higher risk in patients with the severe form of COVID-19 with several comorbidities associated. Our results showed that cerebrovascular disease had the highest OR value of 2.76 (95 % CI: 1.65–4.62; I 2 = 44 %; p = 0.06) [ 19 , 21 , 28 , 31 33 , 38 40 , 44 , 45 ] despite the fact that no significant difference between patients with severe and non-severe cerebrovascular disease was reported after analysis. This risk is followed by chronic kidney disease (CKD), with an OR of 2.27 (95 % CI: 1.26–4.06]; I 2 = 96 %; P < 0.001) [ 15 , 18 , 19 , 22 , 24 , 26 35 , 37 , 38 , 42 , 44 , 45 ], hypertension with an OR of 2.22 (95% CI: 1.72–2.87; I 2 = 96 %; p < 0.001) [ 14 40 , 42 46 ] and coronary heart disease with an OR of 2.17 (95 % CI: 1.42–3.31; I 2 = 98 %; p < 0.001) [ 15 , 18 22 , 24 46 ].…”
Section: Resultsmentioning
confidence: 65%
“…Our results showed that cerebrovascular disease had the highest OR value of 2.76 (95 % CI: 1.65–4.62; I 2 = 44 %; p = 0.06) [ 19 , 21 , 28 , 31 33 , 38 40 , 44 , 45 ] despite the fact that no significant difference between patients with severe and non-severe cerebrovascular disease was reported after analysis. This risk is followed by chronic kidney disease (CKD), with an OR of 2.27 (95 % CI: 1.26–4.06]; I 2 = 96 %; P < 0.001) [ 15 , 18 , 19 , 22 , 24 , 26 35 , 37 , 38 , 42 , 44 , 45 ], hypertension with an OR of 2.22 (95% CI: 1.72–2.87; I 2 = 96 %; p < 0.001) [ 14 40 , 42 46 ] and coronary heart disease with an OR of 2.17 (95 % CI: 1.42–3.31; I 2 = 98 %; p < 0.001) [ 15 , 18 22 , 24 46 ]. Other significant judgment criteria for risk factors of the comorbidities involved in the severe form of COVID-19 included chronic obstructive pulmonary disease (COPD) (OR: 1.95, 95% CI: 1.22–3.09; I 2 =98%, p < 0.001) [ 14 , 15 , 19 23 , 25 28 , 30 32 , 34 36 , 38 42 , 44 , 45 ], diabetes mellitus (OR=1.81, 95% IC: 1.35–2.43; I 2 =97 %, p<0.001) [ ...…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…There was a significant reduction in lymphocyte, monocyte, eosinophil, and platelet counts as well as hemoglobin levels in severe cases compared with mild and moderate cases [ 33 ]. The study also highlighted the higher neutrophil count, ALT, AST, creatinine, and BUN in COVID-19 patients with severe symptoms and possible admission to the ICU [ 3 , 34 ]. Other biomarkers, such as LDH, PT, and D-dimer, were also associated with the severity of the disease and admission to the ICU [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…On 30 January 2020, the World Health Organization (WHO) officially declared the COVID-19 pandemic as a public health emergency of international concern [ 1 , 2 ]. Symptoms are usually mild, ranging from fever with a dry cough to sore throat, breathlessness, and fatigue [ 3 ]. However, vulnerable patients, such as the elderly and those with comorbidities, are at a higher risk of severe complications, including pneumonia, acute respiratory distress syndrome (ARDS), and multiorgan dysfunction [ 4 ].…”
Section: Introductionmentioning
confidence: 99%